1976
DOI: 10.1172/jci108550
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of portal hypertension-induced alterations in renal hemodynamics, renal water excretion, and renin secretion.

Abstract: A B S T R A C T Clinical states with portal venous hypertension are frequently associated with impairment in renal hemodynamics and water excretion, as well as increased renin secretion. In the present investigation, portal venous pressure (PVP) was increased in anesthetized dogs undergoing a water diuresis. Renal arterial pressure was maintained constant in all studies. As PVP was increased from 6 to 20 mm Hg, decreases in cardiac output (2.5-2.0 liter/min, P < 0.05) and mean arterial pressure (140-131 mm Hg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 26 publications
1
27
1
Order By: Relevance
“…In agreement with these results, it has been reported that an acute increase in portal venous pressure due to the extraluminal obstruction of the portal vein causes a reduction of arterial blood pressure, cardiac output, renal blood flow, and glomerular filtration rate (LIANG, 1971;LEVY, 1974;ANDERSON et al, 1976). When portal venous pressure exceeded appoximately 30 cmH2O, arterial blood pressure significantly fell and glomerular filtration rate was reduced significantly (LEVY, 1974;ANDERSON et al, 1976). LEVY (1974) reported, in addition, that portal venous hypertension did not appear to modify renal function unless systemic hypotension coexisted.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In agreement with these results, it has been reported that an acute increase in portal venous pressure due to the extraluminal obstruction of the portal vein causes a reduction of arterial blood pressure, cardiac output, renal blood flow, and glomerular filtration rate (LIANG, 1971;LEVY, 1974;ANDERSON et al, 1976). When portal venous pressure exceeded appoximately 30 cmH2O, arterial blood pressure significantly fell and glomerular filtration rate was reduced significantly (LEVY, 1974;ANDERSON et al, 1976). LEVY (1974) reported, in addition, that portal venous hypertension did not appear to modify renal function unless systemic hypotension coexisted.…”
Section: Discussionsupporting
confidence: 79%
“…It was reported that increases in renal sympathetic activity produced increases in renin secretion from the kidney (KOYAMA et al, 1980(KOYAMA et al, , 1981AMMONS et a!., 1982). ANDERSON et al (1976) also demonstrated that increases in portal venous pressure resulted in increases in renin secretion mediated by activation of renal symapthetic tone.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations